Ds C Spoelstra en die Nederduitsch Hervormde Kerk - Bruin, C. J. du (Hervormde teologiese studies, 1998)
Rev C Spoelstra and the Nederduitsch Hervormde Kerk. The inter relationship between 'Rev C Spoelstra and the Nederduitsch Hervormde Kerk' is studies from three different perspectives: Spoelstra with or as part of the church (a positive relationship). Secondly, there is the increasing tension between Spoelstra and Rev M J Goddefroy (Goddefroy eventually became to Spoelstra the representation of the whole Nederduitsch Hervonnde Kerk). Thirdly, Spoelstra opposed the whole Nederduitsch Hervormde Kerk and not only Goddefroy.